2014
DOI: 10.1111/jam.12626
|View full text |Cite
|
Sign up to set email alerts
|

Do the intestinal microbiotas differ between paddlefish (Polyodon spathala ) and bighead carp (Aristichthys nobilis ) reared in the same pond?

Abstract: Aims: A study was conducted to compare the intestinal microbial compositions of two fish species with similar feeding strategy; paddlefish (Polyodon spathala) and bighead carp (Aristichthys nobilis) reared in the same pond. Methods and Results: Age-0 paddlefish and bighead carp with mean average body lengths of 43Á39 AE 2Á78 and 19Á33 AE 3Á68 cm, respectively, were reared with natural prey items in the same pond (20 m 2 ). After 30 days of rearing, the intestinal microbiota of the two fish species was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 39 publications
9
45
0
Order By: Relevance
“…Although most of our isolates appear closely related, the fact that every fish and habitat we examined contained different isolates suggests that there are many diverse and unique strains of Shewanella that are adapted to specific ecological niches. In support of this hypothesis, it was recently reported that the intestinal microbiota of fish can be very specific to the fish species they colonize (70).…”
Section: Discussionmentioning
confidence: 77%
“…Although most of our isolates appear closely related, the fact that every fish and habitat we examined contained different isolates suggests that there are many diverse and unique strains of Shewanella that are adapted to specific ecological niches. In support of this hypothesis, it was recently reported that the intestinal microbiota of fish can be very specific to the fish species they colonize (70).…”
Section: Discussionmentioning
confidence: 77%
“…It is of interest to note that the most dominant genus in male and female largemouth bronze gudgeon was unclassified bacteria (phylum Proteobacteria and family Enterobacteriaceae) and Mycoplasma (phylum Tenericutes), respectively, which is different to the findings reported for other freshwater fish species [28, 38]. Ringø et al [9] showed that the abundance of Enterobacteriaceae were affected by protein sources.…”
Section: Discussionmentioning
confidence: 88%
“…The exterior surfaces were swabbed with 75 % ethanol before dissection of the whole intestine using sterile instruments (scissors and tweezers). The intestine of each individual fish was dissected out, and similar weight (about 0.2 g) of foregut, midgut and hindgut from each individual was collected and pooled together into a sterile tube as a single sample as described previously [38]. The individual intestinal contents were homogenized by vortexing briefly.…”
Section: Methodsmentioning
confidence: 99%
“…Proteobacteria was the most prevalent phylum in the examined fish. This commonly‐found phylum was also observed in the intestines of other freshwater fish, such as: bighead carp Hypophthalmichthys nobilis (Richardson 1845) (Li et al ., ) and rainbow trout Oncorhynchus mykiss (Walbaum 1792) (Navarrete et al ., ). An analogous situation was observed in Midas cichlid Amphilophus citrinellus (Günther 1864) freshwater fish (Franchini et al ., ).…”
Section: Discussionmentioning
confidence: 97%